Social Exchange Theory (SET) as a Framework for Understanding Retailer- Supplier Relationship Quality. (Global Business Management Review (GBMR), 2022)
This paper proposes the applicability and justifications for using social exchange theory (SET) as the underlying theory for explaining relationship quality in the retail industry. The study opens up new horizons in expanding the readers and future researchers in developing research frameworks with the underlying premises offered by Social Exchange Theory (SET). This paper also contributes to the literature by introducing a new theoretical foundation for measuring the extent of the relationship quality between retailers and their suppliers. This theory can be used by any participant (member) in a retail industry to identify the level of collaboration between the B2B partners and seek further improvement.